If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(a + -10) = 12 Reorder the terms: 6(-10 + a) = 12 (-10 * 6 + a * 6) = 12 (-60 + 6a) = 12 Solving -60 + 6a = 12 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '60' to each side of the equation. -60 + 60 + 6a = 12 + 60 Combine like terms: -60 + 60 = 0 0 + 6a = 12 + 60 6a = 12 + 60 Combine like terms: 12 + 60 = 72 6a = 72 Divide each side by '6'. a = 12 Simplifying a = 12
| 260+6x=11y | | 4n-3=35 | | 5a+2b=0 | | 8x+2(1.5x)=84.61 | | 8x+2(1.5x)=96.15 | | 10t-16=44 | | 8x+2(1.5x)=88.46 | | -7x+9y=24 | | 8x+2(1.5x)=126.92 | | 100=1+9d | | 2x+15=2x-3 | | 18x^2+7x-72=0 | | 8x+2(1.5x)=61.53 | | 8-3/4x=1/2x | | 14.7x+3.1x+7.2= | | 8x+2(1.5x)=69.23 | | 20=2(pi)r | | 8x+2(1.5x)=123.94 | | 4/5x-3-9/4x-6 | | 7x+21-(4x-1)=2 | | 8x+2(1.5x)=53.84 | | 6x+2x=7x+8 | | -1/2(6x-14) | | 10+10y=30 | | 8x+2(1.5x)=115.38 | | 8+6b=50 | | 13=9v+13 | | 2=(x-36.6)/2.5 | | 2x-4=-11+3 | | 3x-33=2x+52 | | 8x+4(1.5x)=84.61 | | X/9-x/7=4 |